Effect of vulcanization time on crosslink density and aging performance of natural rubber composites - Dayioglu, Ahu Kor; Balaban, Seda; Ünür Yılmaz, Ece (Carl Hanser Verlag, 2020)
Natural rubber composites are widely used in the automotive industry because of their improved viscoelastic characteristics that are mostly governed by crosslink density. However, rubber parts suffer deterioration of performance over long service lives. Therefore, optimization of crosslink density and prediction of changes in physico-mechanical properties over time at elevated temperatures is extremely important for the production of safe auto parts. In this work, the effect of vulcanization time on crosslink density and thus the performance and lifetime of natural rubberbased auto parts was investigated. The natural rubber mixture prepared in this context was vulcanized for 3, 5, 10 and 15 minutes at a constant temperature of 160 degrees C. The crosslink density of each vulcanizite was determined by equilibrium swelling tests and the Flory-Rehner equation. The maximum crosslink density (10.75 x 10(-5) mol x cm (-3)) and the minimum permanent compression set values (10% at 70 degrees C and 25% at 100 degrees C) were recorded for the sample vulcanized for 10 minutes (V-10). Aging behavior of the samples were investigated by stress relaxation tests performed at 85 degrees C, 100 degrees C and 120 degrees C. The service lives of the vulcanizites at different temperatures were predicted by linear Arrhenius fits of degradation times. The sample vulcanized for 10 minutes (V-10) was shown to exhibit a service life of 2282 hours at 70 degrees C in air and the optimum physico-mechanical performance under real operating conditions. The performance and lifetime prediction procedure used in this work could be employed in an early design of rubber components for specific applications.
Keywords: Natural rubber; vulcanization time; crosslink density; service life; Arrhenius model